2013
DOI: 10.1055/s-0033-1343430
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs Reduce the Production of Quorum Sensing Regulated Virulence Factors and Swarming Motility in Human Pathogen Pseudomonas aeruginosa

Abstract: Antibiotics are commonly used for the treatment of microbial infections. With the widespread appearance of multi antibiotic-resistant bacteria, it is becoming increasingly more difficult to treat bacterial infections with conventional antibiotics. Thus, there is an increasing need for new strategies to cope with infectious diseases. The discovery that many pathogenic bacteria employ quorum sensing (QS) to regulate their pathogenicity and virulence factor production makes the QS system an attractive target for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
(13 reference statements)
5
12
0
1
Order By: Relevance
“…It is considered that this kind of effect should be due to inhibition of bacterial initial attachment (Demirag, Esen, Zivalioglu, Leblebicioglu, & Keceligil, ; Muller, Al‐Attar, Wolff, & Farber, ), reduction of EPS and protein syntheses (Farber & Wolff, ; Muller et al., ), and change of hydrophobicity (Naves et al., ). Another possible interpretation for biofilm inhibition is their impact on the QS system (Ulusoy & Bosgelmez‐Tinaz, ). QS system is a bacterial communication process that depends on the bacterial population density.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that this kind of effect should be due to inhibition of bacterial initial attachment (Demirag, Esen, Zivalioglu, Leblebicioglu, & Keceligil, ; Muller, Al‐Attar, Wolff, & Farber, ), reduction of EPS and protein syntheses (Farber & Wolff, ; Muller et al., ), and change of hydrophobicity (Naves et al., ). Another possible interpretation for biofilm inhibition is their impact on the QS system (Ulusoy & Bosgelmez‐Tinaz, ). QS system is a bacterial communication process that depends on the bacterial population density.…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐inflammatory drugs diclofenac and also ketoprofen were shown to inhibit swarming motility of P. aeruginosa at 5 m m concentration without any growth inhibition. Reduced production of virulence factors as well as activity in an AHL‐quorum‐sensing inhibition screen suggested that these compounds inhibited swarming through the quorum‐sensing circuits with the molecular targets yet to be identified . A diazaborine‐based copolymer with quorum‐sensing inhibitory activity in a violacein assay showed swarming inhibition by about 50 % against P. aeruginosa PAO1 at a concentration of 100 μg mL −1 , whereas the MIC (minimal inhibitory concentration) was determined to be 10 times higher .…”
Section: Swarming and Bacterial Signalingmentioning
confidence: 99%
“…By contrast, several β‐lactams, such as piperacillin ( 4 ) and cephalosporin antibiotics (see below) appeared to further enhance the expression of virulence factors. Because of the previously established roles of anti‐inflammatory agents as potential quorum quenchers in P. aeruginosa , we focused on the effects of cephalosporins and guanfacine. We have herein not addressed the effects of anti‐Parkinson's drugs further, but this topic certainly deserves further attention.…”
Section: Resultsmentioning
confidence: 99%